1967
DOI: 10.1126/science.158.3800.519
|View full text |Cite
|
Sign up to set email alerts
|

Reversal Learning and Forgetting in Bird and Fish

Abstract: Pigeons and goldfish were trained in red-green discrimination in daily sessions, with the rewarded color changed every 2 days. Improvement in the performance of the pigeons could be traced to decrements in retention from each day to the next. The goldfish showed no improvement and no decrements in retention. The results suggest that progressive improvement in habit reversal is a product of proactive interference, and that the absence of improvement in the fish is due, not to the lack of some higher-order proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
48
2

Year Published

1971
1971
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 8 publications
1
48
2
Order By: Relevance
“…While quantitative differences in learning between vertebrate species are to be expected, qualitative differences in learning could severely compromise the translational relevance of animal models [10]. One such potential qualitative difference has been suggested in terms of the performance of fish in reversal learning procedures [11][12][13]. Different species may solve reversal learning problems in different ways, which may indicate different degrees of behavioural flexibility, the ability to 'learn rules' [10] or, more specifically, a shift in stimulus control from simple stimulusreinforcer learning to a more generalised, rule-based approach [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While quantitative differences in learning between vertebrate species are to be expected, qualitative differences in learning could severely compromise the translational relevance of animal models [10]. One such potential qualitative difference has been suggested in terms of the performance of fish in reversal learning procedures [11][12][13]. Different species may solve reversal learning problems in different ways, which may indicate different degrees of behavioural flexibility, the ability to 'learn rules' [10] or, more specifically, a shift in stimulus control from simple stimulusreinforcer learning to a more generalised, rule-based approach [14].…”
Section: Introductionmentioning
confidence: 99%
“…When the animal reaches a set criterion (e.g., 80% correct in a given number of choices, or n consecutive correct choices) the reinforced alternative is switched with the previously unreinforced alternative (i.e., A− B+). In many species (e.g., rats, pigeons, monkeys and humans), despite a high number of errors typically during the initial reversal, the number of errors decreases as a function of subsequent reversals [12,15,16]. A number of potential reasons for this systematic improvement in performance have been suggested, but appear to be related to executive processes during continued learning [17].…”
Section: Introductionmentioning
confidence: 99%
“…Directly below each stimulus patch was a pecking key. In this respect, the apparatus differed from that of Gonzales et al (1967), in which red and green stimuli were projected directly on the pecking keys. A food tray was centered between and below the keys.…”
Section: Apparatusmentioning
confidence: 99%
“…The apparatus was similar to that used by Gonzales et al (1967). The operant conditioning chamber contained an intelligence panel with two 3-cm circular stimulus patches located 10 cm apart and 20 cm above the floor.…”
Section: Apparatusmentioning
confidence: 99%
“…Table 1 also presents data relevant to one interpretation of differences in reversal performance. Gonzalez, Behrend, & Bitterman (1967) have suggested that a decline in errors over reversals may be due to a decline in i nter f eren ce bet we en sliccessive problems; if Ss come to forget from one day to the next which alternative was last conect, they will make fewer errors at the outset of each new problem. Gonzalez et al suggested that goldfish might be inefficient reversal learners because they do not forget.…”
mentioning
confidence: 99%